1995
DOI: 10.1159/000267859
|View full text |Cite
|
Sign up to set email alerts
|

The Blood-Aqueous Barrier in Eyes with Pseudoexf oliation Syndrome

Abstract: Eyes with pseudoexfoliation syndrome (PEX) frequently show clinical signs of impairment of the blood-aqueous barrier. Herein we give an overview of recent studies that analyzed the blood-aqueous barrier in eyes with PEX. Methods: The authors review and summarize recent studies including quantification of aqueous flare in eyes with PEX using the laser flare cell meter (LFCM; Kowa FC-1000) in comparison with normal eyes and eyes with primary open-angle glaucoma (POAG), quantification of aqueous flare in eyes wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
4
11

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(73 citation statements)
references
References 21 publications
3
55
4
11
Order By: Relevance
“…In contrast to our results, previous studies did not find a difference in the impairment of blood-acqueous barrier, measured by means of laser flare-cell meter, between eyes with and without capsular glaucoma (Kuchle et al 1992(Kuchle et al , 1995.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our results, previous studies did not find a difference in the impairment of blood-acqueous barrier, measured by means of laser flare-cell meter, between eyes with and without capsular glaucoma (Kuchle et al 1992(Kuchle et al , 1995.…”
Section: Discussioncontrasting
confidence: 99%
“…The affected iris vessels show a progressive and randomly distributed degeneration of smooth muscle cells, perycites and endothelial cells, in association with pseudoexfoliation material accumulation in their adventitia (Ringvold 1970(Ringvold , 1970bSpinelli et al 1985;Shimizu 1985;Konstas et al 1993;Naumann et al 1998). Considering the wide shade of vascular impairment typical of PXS, the difference in the employed techniques, and the limited number of patients taken into examination by our and others' studies (Kuchle et al 1992(Kuchle et al , 1995Moreno-Montañ és & Blesa 1995), it may be difficult to achieve an exact correlation between histologic damage and degree of blood-aqueous barrier impairment in cases affected or not affected by capsular glaucoma. Moreover, we should bear in mind that the integrity of the blood-aqueous barrier could be influenced by other factors including age of patients, duration and severity of PXS, stage of glaucoma, medical or surgical antiglaucoma therapy.…”
Section: Discussionmentioning
confidence: 82%
“…In many studies cataract surgery in the presence of PEX has been reported to be associated with increased risk of intraoperative and postoperative complications such as zonular dialysis, vitreous loss, prolonged corneal edema, sustained inflammatory reaction and lens decentration [6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25]. Zonular instability, poorly dilating pupils, corneal endothelial changes and breakdown of the blood-aqueous barrier are the leading factors in increased intraoperative and postoperative complications in eyes with PEX [7, 14,26,27,28,29,30,31]. …”
Section: Introductionmentioning
confidence: 99%
“…Iris involvement is histologically expressed by iris vasculopathy, with degeneration of smooth muscle cells, pericytes, and endothelial cells, pseudoexfoliation material deposits at the periphery of iris vessels, with thickening and reduplication of basement membranes. 1,2 The reported histological changes are the morphological correlate of the blood-aqueous barrier (BAB) breakdown, which can be studied by means of several techniques, including fluorophotometry, 3 laser flare-cell meter, [4][5][6] immunohistochemical tracer, 7 and iris angiography. 3,[8][9][10][11] Typical features of PES on iris angiography are hypoperfusion, microneovascularizations, and anastomotic vessels.…”
Section: Introductionmentioning
confidence: 99%